1994
DOI: 10.1007/bf00122394
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval study of stainless steel and titanium miniplates and screws used in maxillofacial surgery

Abstract: The surfaces of 43 stainless steel miniplates and 19 titanium miniplates with matching screws of the same materials were studied after retrieval with respect to surface degradation. Stereomicroscopic and scanning electron microscopic (SEM) examinations were performed, and surface roughness and hardness of the plates were measured. Defects of mechanical nature which could be traced back to handling procedures were found in all stainless steel and titanium devices. Metal tongues and splinters were occasionally f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 16 publications
0
13
0
1
Order By: Relevance
“…In some cases the products of corrosion were found around the blood vessels, in keeping with the findings of MEACHIM and WILLIAMS 19 and TORGERSEN et al 33 , in a histological study of soft tissue adjacent to titanium implants. The observation of metal particles located intracellularly or in association with vessels may represent a biological response aimed at eliminating the foreign material 19,30,32 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases the products of corrosion were found around the blood vessels, in keeping with the findings of MEACHIM and WILLIAMS 19 and TORGERSEN et al 33 , in a histological study of soft tissue adjacent to titanium implants. The observation of metal particles located intracellularly or in association with vessels may represent a biological response aimed at eliminating the foreign material 19,30,32 .…”
Section: Discussionmentioning
confidence: 99%
“…The formation of metal particles increases the surface area available for oxidation and ion release 9,27 . Owing to the lack of consistent information on the long-term effects of metal implants on the human body, an international study group has suggested that all non-functional implants should be evaluated for removal 31,32 .…”
Section: Discussionmentioning
confidence: 99%
“…Verificou-se que a composição química da placa (inicialmente declarada como sendo liga Ti-6Al-4V ) não estava de acordo com as exigências mínimas da norma NBR-ISO: 5832-3 (ABNT, 1997b) para esta liga (Tabela 3). Entretanto, placas usadas em cirurgias buco-maxilo-faciais geralmente são fabricadas em ligas de titânio comercialmente puro (CP Ti), e de fato a composição quí-mica e o tamanho de grão metalúrgico da placa analisada estão de acordo com os requisitos da norma NBR-ISSO: 5832-2 (ABNT, 1997a), grau 1 (CP Ti) (Torgensen & Gjerdet, 1995). A composição química dos parafusos se adequou, via de regra, às especificações para a liga Ti-6Al-4V.…”
Section: Procedimento Experimental E Resultadosunclassified
“…Metal tongues and splinters were also seen associated with screw threads and in the periphery of plate screw holes. Jorgensen and Gjerdet [2] in their study of SS and titanium miniplates and screws concluded that Defects of mechanical nature were found in all SS [8].…”
Section: Discussionmentioning
confidence: 99%